2022
DOI: 10.1186/s12885-022-09469-5
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan plus temozolomide in relapsed Ewing sarcoma: an integrated analysis of retrospective studies

Abstract: Background The prognosis of patients with relapsed Ewing sarcoma is poor. In this study, we aimed to pooled-analyze the efficacy and safety of the combination of irinotecan and temozolomide in treating patients with relapsed Ewing sarcoma. Methods PubMed, Cochrane CENTRAL, Web of Science, and EMBASE were systematically searched on September 27, 2021. The primary outcomes were rates of objective response and disease control, and the secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The pharmacological activation of irinotecan (or CPT-11) involves the participation of carboxylesterases (CE) to generate the active metabolite SN-38, a promising prodrug for the treatment of STS [ 17 ]. Earlier, both irinotecan and temozolomide proved to be effective in Ewing sarcoma clinical trials [ 18 , 19 , 20 , 21 ], and this encouraged the evaluation of these compounds in RMS. A phase II study from the STSC (2002–2004) revealed an interesting response rate of refractory and recurrent STS patients, including RMS, to irinotecan [ 22 ].…”
Section: The Evolution Of the Treatment For Rms And Recent Clinical T...mentioning
confidence: 99%
“…The pharmacological activation of irinotecan (or CPT-11) involves the participation of carboxylesterases (CE) to generate the active metabolite SN-38, a promising prodrug for the treatment of STS [ 17 ]. Earlier, both irinotecan and temozolomide proved to be effective in Ewing sarcoma clinical trials [ 18 , 19 , 20 , 21 ], and this encouraged the evaluation of these compounds in RMS. A phase II study from the STSC (2002–2004) revealed an interesting response rate of refractory and recurrent STS patients, including RMS, to irinotecan [ 22 ].…”
Section: The Evolution Of the Treatment For Rms And Recent Clinical T...mentioning
confidence: 99%
“…Irinotecan has been evaluated in many clinical trials in different tumor types [26,[53][54][55]. We provide an overview of sarcoma trials in Table 1.…”
Section: Irinotecan (Camptothecin-11)mentioning
confidence: 99%
“…1,2 Depending on location and timing of relapse, traditional approaches to second line therapy have been dominated by cytotoxic chemotherapies. 3,4 However, outcomes with cytotoxic chemotherapy remain poor and the recently published studies reporting the activity of tyrosine kinase inhibitors (TKIs) in patients with relapsed bone tumours were met with great hope. [5][6][7][8] Tyrosine kinases are key signalling proteins involved in cell growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%